2007
DOI: 10.1186/1477-7819-5-94
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter species are associated with possible increase in risk of biliary lithiasis and benign biliary diseases

Abstract: Background: Hepato-biliary tract lithiasis is common and present either as pain or as asymptomatic on abdominal ultrasonography for other causes. Although the DNA of Helicobacter species are identified in the gallbladder bile, tissue or stones analyzed from these cases, still a causal relationship could not be established due to different results from different geographical parts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…9 Evidence supporting the association between H. pylori infection and gallbladder diseases can be found by using a direct culture or staining method of H. pylori in gallbladder tissue, as well as indirect techniques, such as the polymerase chain reaction, enzyme-linked immunosorbent assay (ELISA), and serology for the detection of H. pylori-specific antibodies. [10][11][12] The H. pylori positive rate in the gallbladder is reported to be approximately 10-20% by culture, 13 and the presence of H. pylori in the gallbladder mucosa was first confirmed by Kawaguchi et al in 1996. 14 Although H. pylori has been found to occur 3.5 times more frequently in chronic cholecystitis, whether it contributes to the pathogenesis of biliary disease is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…9 Evidence supporting the association between H. pylori infection and gallbladder diseases can be found by using a direct culture or staining method of H. pylori in gallbladder tissue, as well as indirect techniques, such as the polymerase chain reaction, enzyme-linked immunosorbent assay (ELISA), and serology for the detection of H. pylori-specific antibodies. [10][11][12] The H. pylori positive rate in the gallbladder is reported to be approximately 10-20% by culture, 13 and the presence of H. pylori in the gallbladder mucosa was first confirmed by Kawaguchi et al in 1996. 14 Although H. pylori has been found to occur 3.5 times more frequently in chronic cholecystitis, whether it contributes to the pathogenesis of biliary disease is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous meta-analysis demonstrated that Helicobacter pylori ( H.pylori ) in human biliary system was correlated with chronic cholecystitis, especially in the regions with higher prevalence of this infectious agent such as South Asia, East Asia and Latin America. [6] Evidences supporting the association between H.pylori infection and chronic cholecystitis could be found by using direct culture or staining of H.pylori in gallbladder tissues as well as indirect techniques such as PCR, ELISA and serology for detecting H.pylori -specific genes or antibodies [7][9]. The positive rate of H.pylori in gallbladder is reported to be 10%–20% by culture.…”
Section: Introductionmentioning
confidence: 99%
“…in biliary tract and stone diseases. Some reported strong positive correlation while others indicated totally negative results [7][9]. To understand these controversial findings, the following three premises should be concerned.…”
Section: Introductionmentioning
confidence: 99%